Biochemical Mapping of the Inflamed Human Dental Pulp - Konstantina Kritikou (MDPI AG, 2021)
Dental pulp inflammation, caused by the evolution of caries, involves numerous interrelated activities at a cellular and molecular level. Cytokines, proteases, growth factors, and other biomarkers of the host response may take part in dental pulp’s immune defense. The aim of this pilot study was to determine the levels of inflammation, oxidative stress, and extracellular matrix degradation biomarkers in healthy and symptomatic irreversibly inflamed dental pulp samples from children and adolescents. Twenty-three dental pulp samples were collected from permanent teeth with irreversible inflammation, while nineteen healthy dental pulp samples were obtained from teeth extracted for orthodontic reasons. Pulp lysates were obtained and the levels of IL-2, IL-17, TNF-α, SOD3, TGF-β1, catalase, osteocalcin, MMP-7, and MMP-9 were determined using the enzyme-linked immunosorbent assay (ELISA) technique. We detected significantly higher levels (p < 0.001) of IL-2, IL-17, TNF-α, SOD3, osteocalcin, and TGF-β1 in pulp samples with irreversible inflammation than in controls. Catalase and MMP-7 showed higher levels in the experimental group, while MMP-9 showed slightly increased levels in the control group, but none of these differences were statistically significant (p = 0.064/p = 0.061/p = 0.625). Inflamed dental pulp samples showed an up-regulation of IL-2, IL-17, TNF-α, SOD3, osteocalcin, and TGF-β1. These biomarkers appear to have a powerful role in the inflammation process of human dental pulp.